2011
DOI: 10.1002/jemt.20903
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of lead and cadmium released by cigarette smoke in dental structures and resin composite

Abstract: Cigarette smoke is a significant source of cadmium, lead, and toxic elements, which are absorbed into the human organism. In this context, the aim of this study was to investigate in vitro the presence of toxic elements, cadmium, and lead deriving from cigarette smoke in the resin composite, dentine, and dental enamel. Eight cylindrical specimens were fabricated from resin composite, bovine enamel, and root dentin fragments that were wet ground and polished with abrasive paper to obtain sections with 6-mm diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
3
24
0
1
Order By: Relevance
“…In this study, the exposure to cigarette smoke was also able to increase the surface roughness and staining of composite resin, in agreement with other studies that have shown the smoke can influence on chemical and mechanical properties of resinous materials 13,17,25,30 .The surface roughness showed by the composite resin exposed to cigarette smoke did not differ from other groups, regardless of the presence of SBAP. The roughness changes of resin exposed to smoke can be attributed to combustion process of organic matter present in tobacco, resulting in presence of carbon monoxide and carbon dioxide, among other harmful substances besides the increase of temperature 13,31 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the exposure to cigarette smoke was also able to increase the surface roughness and staining of composite resin, in agreement with other studies that have shown the smoke can influence on chemical and mechanical properties of resinous materials 13,17,25,30 .The surface roughness showed by the composite resin exposed to cigarette smoke did not differ from other groups, regardless of the presence of SBAP. The roughness changes of resin exposed to smoke can be attributed to combustion process of organic matter present in tobacco, resulting in presence of carbon monoxide and carbon dioxide, among other harmful substances besides the increase of temperature 13,31 .…”
Section: Discussionsupporting
confidence: 91%
“…Besides the SBAP's abrasive effect on composite resin surface, other substances are able to alter the resin matrix, elevating the superficial roughness and thus the degradation of the material [24][25][26] . The exposure to coffee increased the resin surface roughness and stain- ing if compared to control group, independently of the association to SBAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the increase in water sorption in samples exposed to cigarette smoke, these results are in accordance with the results presented by Takeuchi et al 20 and Mathias et al 16 who stated that the chemical elements present in cigarette smoke are incorporated into the structure and alter the surface of the resin. Additionally, Vitoria et al 21 demonstrated that cigarette smoke enhances the diffusion dynamics of adhesive system liquids by reducing their physical properties.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, Takeuchi et al 20 concluded in an in situ study that both enamel and composite resin had their color and microhardness altered by cigarette smoke. In this study, higher values of solubility were for composite resin exposed to cigarette smoke, regardless of the air-polishing procedure.…”
Section: Discussionmentioning
confidence: 99%